Implementasi Kebijakan Publik Tentang Penataan dan Pemberdayaan Pedagang Kaki Lima (PKL) - Ibnu Sulthan Suneth; Hadi Ismanto (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2014)
The purposes of this research were to describe policy implementation of planning and empowering street vendors in Sidoarjo regency and its effects. Method of this research used qualitative approach. The results of this research showed that the Sanitation Department had many obstacles to implement this policy related with uncorporate between local government and many departments that involved in this policy implementation. So, there were problem still dicuss in local legislators in order to the mandate of Permendagri number 41 of 2012 on Structuring and Empowering of Street Vendors (PKL) can be realized particular in Sidoarjo Regency. Positive impact in this policy implementation for community could fulfill their needs, while negative impacts were uncomfortable condition when the street vendors sell in public area, highway, and sidewalk.